Managerial skills as a determinant of international negotiation - Gonzalez Marin, Yesid; Arias Vargas, Francisco Javier; Garcés Giraldo, Luis Fernando; Gonzalez Marin, Yesid; Arias Vargas, Francisco Javier; Garcés Giraldo, Luis Fernando; Gonzalez Marin, Yesid; Arias Vargas, Francisco Javier; Garcés Giraldo, Luis Fernando (Corporación Universitaria Americana, 2022)
Introduction: The development of managerial skills during the last two decades, in managers, makes a great difference in the effectiveness of employees and theorganization's overall performance. The difficulties evoked by managers involved in international business are due to socio-cultural differences, legal conditions, and lifestyles. Objective: To analyze managerial skills as a function of international business. Reflection: Under a commercial relations approach, managerial skills are acquired and learned to produce expected results with maximum certainty that allow companies to expand their markets globally. Conclusions: The traditional approaches referred to managerial skills in terms of the competencies to be achieved by managers in organizations are based on leadership, understood as the ability to train and developcommon actions, under common objectives.